2017
DOI: 10.1021/acs.jproteome.6b00912
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Links between Diet and Health in an Irish Cohort: A Lipidomic Approach

Abstract: The UCD community has made this article openly available. Please share how this access benefits you. Your story matters! (@ucd_oa) Some rights reserved. For more information, please see the item record link above. AbstractEpidemiology and clinical studies provide clear evidence of the complex links between diet and health. To understand these links, reliable dietary assessment methods are pivotal. Biomarkers have emerged as more objective measures of intake compared to traditional dietary assessment methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The MECHE cohort study group previously highlighted inflammatory and metabolic biomarkers and altered genes expression in an age and BMI‐dependent manner . However to date there was little appreciation of the gender dependency in terms of metabolic responses to metabolic challenges, which is potentially important since gender greatly influence dietary intake and nutrient responses . Studies have reported association between obesity, inflammatory biomarkers, and gender with a stronger correlation in women than men …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MECHE cohort study group previously highlighted inflammatory and metabolic biomarkers and altered genes expression in an age and BMI‐dependent manner . However to date there was little appreciation of the gender dependency in terms of metabolic responses to metabolic challenges, which is potentially important since gender greatly influence dietary intake and nutrient responses . Studies have reported association between obesity, inflammatory biomarkers, and gender with a stronger correlation in women than men …”
Section: Discussionmentioning
confidence: 99%
“…An OLTT modulated inflammatory transcriptomic biomarkers in an age and BMI‐dependent fashion, much more than an OGTT, which is often the standard metabolic challenge, to assess T2D risk . To date, the impact of gender as a potential determinant in the transcriptomic response to a metabolic challenge is unknown, despite the fact that men and women differ greatly with respect to dietary intakes and metabolic responses (relating to lipid and/or glucose metabolism) …”
Section: Introductionmentioning
confidence: 99%
“…It is now increasingly used in nutritional studies, especial since commercial companies can deliver lipidome profiles in a robust manner, with increasingly competitive prices. Lipidomics is being used for effect analysis [128,232] but also to monitor dietary exposure [233,234] and the relationship between food intake and health parameters [234,235]. Lipidomics has also been useful to provide some insights into metabolic pathways by which food exposure may exert its health effects [235].…”
Section: Nutrigenomic Approach In the Identification Of Biomarkersmentioning
confidence: 99%
“…In order to strengthen evidence for the application of intake/health efficacy biomarkers, future research should aim to relate food intake biomarkers to diet-related disease risk by (1) taking a pathway- and network-based bioinformatics approach and (2) building on existing transcriptomic and metabolomics data ( 62 ) . O'Gorman et al recently applied this approach in the Metabolic Challenge Study and identified twenty-two lipid biomarkers that were associated with total dietary fat intake ( 63 ) . Five of these twenty-two lipid biomarkers were significantly elevated in participants with increased risk of the metabolic syndrome ( 63 ) .…”
Section: Bridging Dietary Biomarkers To Health Pathwaysmentioning
confidence: 99%
“…O'Gorman et al recently applied this approach in the Metabolic Challenge Study and identified twenty-two lipid biomarkers that were associated with total dietary fat intake ( 63 ) . Five of these twenty-two lipid biomarkers were significantly elevated in participants with increased risk of the metabolic syndrome ( 63 ) . Wittenbecher et al also applied a metabolomics approach and identified six out of twenty-one potential biomarkers for red meat consumption to be associated with type 2 diabetes ( 64 ) .…”
Section: Bridging Dietary Biomarkers To Health Pathwaysmentioning
confidence: 99%